INTEGRATED STUDIES FOR CHARACTERIZATION OF LINEAMENTS USED TO LOCATE GROUNDWATER POTENTIAL ZONES IN A HARD ROCK REGION OF KARNATAKA, INDIA - Chandra S.; Rao V.A.; Krishnamurthy N.S.; Dutta S.; Ahmed Sh. (My University, 2006)
An integrated study was carried out to investigate the subsurface geological conditions in a hard rock environment, with the aim of identifying zones with groundwater resource potential. The study, in Bairasagara watershed, Karnataka, India, considered geomorphology, water level, resistivity imaging, self potential, total magnetic field and susceptibility. The signatures due to lineaments have been clearly identified and their role in groundwater movement has been documented. Synthetic simulation methods were used to model the electrical response of the lineament using finite differential modeling scheme. The inverted image of the field data is compared with the synthetic image and iteration were performed on the initial model until a best match was obtained resulting on the generation of the calibrated resistivity image of the subsurface. Resistivity imaging revealed that the dykes are weathered/fractured to a depth of 6–8 m and are compact at deeper levels, and that they behave as barriers to groundwater movement, yet facilitate a good groundwater potential zone on the upgradient side. The results of magnetic surveys were utilized in differentiating granites and dolerite dykes with an insignificant resistivity contrast. Geomorphological expression alone cannot reveal the groundwater potential associated with a lineament. However, characterizing the nature of the feature at depth with integrated geophysical methods provides essential information for assessing that potential.
Keywords: INTEGRATED STUDIES; LINEAMENTS; GROUNDWATER RESOURCES; ELECTRICAL RESISTIVITY IMAGING (ERI); HARD ROCK